Design of Cash Flow Financial Statement Accounting Information System At Badan Layanan Umum Balai Besar Bahan dan Barang Teknik (B4T) Bandung Using Microsoft Visual Basic 2008 and MySQL Based Client Server (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
Badan Layanan umum Balai Besar Bahan dan barang Teknik (BLU-B4T) Bandung that have an address at Jalan Sangkuriang no. 14 Bandung 40135 telephone 022-2504088 faximile 022-2502027 E-mail: info@b4t.go.id homepage: www.b4t.go.id. The time activity of executing recording and calculating evidances of transaction on receipt service or evidances of transaction on expending that have Badan Layanan Umum Balai Besar Bahan dan Barang Teknik (BLU-B4T) Bandung by using Microsoft excel Software. There situation can resulted a problems on accurating data input that because by no effectif and optimal performance of at division in the agency, that trouble can impacted to reporting that needed by agency. On these problems author takes title "Design of Accounting Information Systems Statement Financial of Cash Flow on BLU-B4T by Using Microsoft Visual basic 2008 Software and Database MySQL Bases of Client Server".